Levo-tetrahydropalmatine attenuates methamphetamine reward behavior and the accompanying activation of ERK phosphorylation in mice. (1st January 2020) - Su, Hongliang; Sun, Tingting; Wang, Xiao; Du, Yan; Zhao, Na; Zhu, Jie; Yan, Jiangwei; Chen, Teng; Yun, Keming
Highlights: Methamphetamine (METH) induced conditioned place preference (CPP) in mice. L-THP attenuated METH-induced CPP in mice. METH induced upregulation of ERK phosphorylation in nucleus accumbens (NAc) and prefrontal cortex (PFc) of mice. L-THP decreased the high expression of ERK phosphorylation induced by METH in NAc and PFc of mice. Abstract: Levo-tetrahydropalmatine (L-THP) is the main active ingredient of traditional Chinese herbal medicine Corydalis and Stephania, which have been used for sedative, neuroleptic, and analgesic purposes. Previous studies have demonstrated that L-THP has antagonistic activation on dopamine receptors. Despite its effectiveness on treating drug addiction, L-THP's underlying molecular mechanisms in modulating methamphetamine (METH) reward behavior remain unclear. In order to clarify the mechanisms behind, we designed an experiment of conditioned place preference (CPP) to investigate the effects of L-THP on METH-induced CPP in mice. We then dissected the underlying molecular mechanisms of L-THP in modulating METH-induced CPP by evaluating accompanying changes in expression of phosphorylated extracellular signal-regulated kinase (p-ERK) in reward-relevant brain regions, including nucleus accumbens (NAc), prefrontal cortex (PFc), caudate putamen (CPu), and hippocampus (Hip), which may mediate the effects of L-THP on METH-induced CPP. The results showed that 1.0 mg/kg METH could induce obvious CPP in mice; 10.0 mg/kg L-THP could significantly attenuate METH-induced CPP in mice, though it could not induce CPP or conditioned place aversion by itself. Moreover, the levels of p-ERK in NAc and PFc of the METH group were significantly higher than that of the saline group. Although there was no evident difference between the levels of p-ERK of the L-THP group with that of the saline group, the levels of p-ERK in NAc and PFc of the M + T group were significantly lower than that of the METH group. There was no striking difference among the levels of p-ERK in CPu and Hip of all experimental groups. Our research suggested that NAc and PFc function as circuits contributing to METH addiction, and the activation of the ERK phosphorylation plays an important role in the mechanisms of METH addiction. Besides, L-THP significantly decreased ERK phosphorylation's high expression induced by METH, which suggested that the inhibitory effect of L-THP on modulating METH reward behavior may be related to the suppression of ERK phosphorylation in NAc and PFc of mice. In conclusion, L-THP could suppress the reward properties of METH, therefore, it may be a promising candidate for the treatment of METH addiction.